Intention to Emigrate in Transition Countries: The Case of Albania - Harry Papapanagos; Peter Sanfey (University of Kent, Department of Economics, 1998)
We analyse the profile of potential emigrants from Albania using data from the Central and Eastern Europe Eurobarometer in 1992. Respondents were asked to rate on a four-point scale the likelihood that they would go to Western Europe to live and work. Our results show that the intention to emigrate is positively correlated with males, education and certain occupations, and negatively correlated with age. There is little relation between emigration and income, but those who believe the country is going in the right direction are also more likely to emigrate than those who do not.
Keywords: F22; O52; P2; 330; Emigration; Transition; Albania; Auswanderung; Arbeitsmigranten; Systemtransformation; Schätzung; Albanien